Изучение анатомии бурой водоросли Jolyna laminarioides Guim. (Phaeophycota) - Аббас, А.; Шамиль, М. (Альгология, 2011)
Представлены результаты изучения морской бурой водоросли Jolyna laminarioides (Scytosiphonaceae, Scytosiphonales, Laminarophyceae), собранной у побережья г. Карачи (Пакистан). Рассматриваются систематик а, анатомия и особенности строения репродуктивных структур водоросли. A marine brown alga Jolyna laminarioides in Guimarães et al. (family Scytosiphonaceae, order Scytosiphonales, class Laminarophyceae, phylum Phaeophycota) was collected during September 2007 – November 2009 from the coast of Karachi (Pakistan) and investigated for its taxonomy, anatomy and reproductive structures. A detailed investigation of its anatomical features was for the first time and is being presented.